El doble testimoni de Miquel Martí i Pol (1957-1972) - Carbó, Ferran (Caplletra. Revista Internacional de Filologia, 2000)
Resum: The essay offers a revisión of Miquel Martí i Pol’s poetry written between 1957 and 1971. This poetry has been regarded by critics as linked to historical realism, and in our opinión consitutes the literary consolidation of the Roda de Ter-born poet after his his apprenticeship in existential poetry. Throughout five books and a long poem, the authorembodies a double social dimensión in his verse: on the one hand, extemal and collective history, especially achieved through the universe of the village and the factory; on the other hand, the inner and personal history dealing with aspects of his most intérnate experience in themes such as love or the function of poetry. Paraules clau: Miquel Martí i Pol; poesia existencial; poesia catalana contemporània